Anti T-lymphocyte Globulin (Grafalon®) Use during Rabbit Anti-thymocyte Globulin (Thymoglobulin®) Shortage – A Single-center Experience - Shailendra Tiwari; Namrata S Rao; Abhilash Chandra; Majibullah Ansari; Sanjeet Kumar Singh (Indian Journal of Transplantation)
Introduction: During a period of local nonavailability of rabbit anti-thymocyte globulin (rATG) in India, anti-T-lymphocyte globulin (ATLG) was utilized in high-risk renal transplantation. The study aimed to compare renal transplant recipients (RTRs) in two study periods with rATG and ATLG induction use, in terms of biopsy-proven acute rejection (BPAR) rates, patient and graft survival and infectious complications in the 1st year and beyond. Methods: This retrospective, single-center study compared two time periods: June 2019–June 2021 (Period I – rATG induction) and July 2021–October 2022 (Period II – ATLG induction). Only immunologically high-risk, ABO-compatible living donor RTRs were included. Clinical data were sourced from hospital information system, and only infections requiring hospital admissions were collected. Missing information was collected telephonically. Results: A total of 78 RTRs were included in the analysis, of whom 28 received rATG at a dose of 3 mg/kg (Period I) and 50 received ATLG at a dose of 5–6 mg/kg (Period II). Delayed and slow graft function (SGF) were significantly increased in Period II (12%, 12% vs. 10.7%, 7.1%, respectively, P < 0.001), trend toward increased BPAR episodes in Period II (12% vs. 10.7%, P = 0.155) and similar death-censored graft survival [60.6 months in Period I vs 73.4 months in Period II (P=0.66)]. Infection-related admissions were significantly lower in Period II. First year rejection-free and infection-free survival plots were similar in the two periods (log-rank test P > 0.05). Conclusion: The use of 5–6 mg/kg dose of ATLG (a relatively low dose) during rATG nonavailability, was associated with higher delayed and SGF, similar BPAR, graft and patient survival rates, and lower risk of infectious complications in immunologically high-risk patients.